Resiliensi Kepala Sekolah PAUD dalam Menyelenggarakan Layanan PAUD di Daerah Industri - Sri Widhiyanti (Universitas Negeri Yogyakarta, 2026)
Education is one of the important things that will provide children in life. School as formal education has the aim of forming human beings with personality, in developing students' intellectuals in order to make the nation's life more intelligent. In line with the needs and developments of the times, currently many formal early childhood schools are emerging. The existing schools for early childhood are diverse in terms of curriculum and quality, there are formal schools that follow the national, national plus and international curriculum. The principal of a school in an institution providing Early Childhood Education is a key factor in developing and maintaining the existence of an institution. This study aims to determine the resilience of Early Childhood Education principals in organizing their institutions that stand in the middle of industrial areas. This research uses qualitative narratives that use stories or experiences from research subjects. From the observations, it was found that the most basic thing that made the principal try to maintain the existence of his institution was because of faith. The principals who have confidence in their profession contribute to the formation of the principal's fighting spirit. In addition, the leadership style and creativity as well as the innovation of the principal are factors that determine an institution can survive in providing its educational services. The school principal's creativity is demonstrated by his ability to generate brilliant ideas related to strategies for providing early childhood services at the early childhood education institution he leads. With these brilliant ideas he will be able to produce changes to advance the institution.